Chitosan-salvianolic acid B coating on the surface of nickel-titanium alloy inhibits proliferation of smooth muscle cells and promote endothelialization - Bi, Shijun; Lin, Hao; Zhu, Kunyuan; Zhu, Zechao; Zhang, Wenxu; Yang, Xinyu; Chen, Shanshan; Zhao, Jing; Liu, Meixia; Pan, Pengyu; Liang, Guobiao (Frontiers in Bioengineering and Biotechnology, 2023)
Intracranial stents are of paramount importance in managing cerebrovascular disorders.Nevertheless, the currently employed drug-eluting stents, although effective in decreasing in-stent 2 This is a provisional file, not the final typeset article restenosis, might impede the re-endothelialization process within blood vessels, potentially leading to prolonged thrombosis development and restenosis over time. This study aims to construct a multifunctional bioactive coating to enhance the biocompatibility of the stents. Salvianolic acid B (SALB), a bioactive compound extracted from Salvia miltiorrhiza, exhibits potential for improving cardiovascular health. We utilized dopamine as the base and adhered chitosan-coated SALB microspheres onto nickel-titanium alloy flat plates, resulting in a multifunctional drug coating. By encapsulating SALB within chitosan, the release period of SALB was effectively prolonged, as evidenced by the in vitro drug release curve showing sustained release over 28 days. The interaction between the drug coating and blood was examined through experiments on water contact angle, clotting time, and protein adsorption. Cellular experiments showed that the drug coating stimulates the proliferation, adhesion, and migration of human umbilical vein endothelial cells. These findings indicate its potential to promote re-endothelialization. In addition, the bioactive coating effectively suppressed smooth muscle cells proliferation, adhesion, and migration, potentially reducing the occurrence of neointimal hyperplasia and restenosis. These findings emphasize the exceptional biocompatibility of the newly developed bioactive coating and demonstrate its potential clinical application as an innovative strategy to improve stent therapy efficacy. Thus, this coating holds great promise for the treatment of cerebrovascular disease.